Implementation of Meaningful Involvement of People Living with HIV/AIDS (MIPA) in HIV/AIDS Programmes in Matobo District of Zimbabwe - Ndhlovu, S.; Matunhu, Jephias (African Journal Online, 2016)
The HIV/AIDS pandemic is anti-development. It robs society of the resources that are akin to development. The MIPA is one of the programmes that have been put in place to help curb the pandemic in Zimbabwe. However, little appears to have been said about the effectiveness of the programme in Matobo District in Matebeleland South in Zimbabwe. This study evaluates the implementation of the programme. A mixed research design was used in the study. Semi-structured questionnaires were used in data collection. The theoretical framework of the study is a combination of the disclosure and the consequence theories of HIV/AIDS. The study concludes that implementation of the MIPA strategy in the district is not effective.